The crystal structure of diaqua-bis[5-(4-methylphenyl)-1H-pyrazole-3-carboxylato-κ2N,O]-cobalt(II), C11H11Co0.5N2O3 - Jiang Yun-hua; Feng Chao; Du Dao-hang; Zhao Hong (Zeitschrift für Kristallographie - New Crystal Structures)
C11H11Co0.5N2O3, Triclinic, P1‾ $P\overline{1}$ , a = 4.8354(4) Å, b = 6.2696(3) Å, c = 18.3717(12)(4) Å, α = 92.763(5)°, β = 94.079(7)°, γ = 103.858(6)°, V = 538.15(6) Å3, Z = 2, R gt(F) = 0.050, wR ref(F 2) = 0.125, T = 293 K.